Improving Vocational High School Students' Learning Motivation Through Digital-Based Interactive Learning Models - Fery Sumatoyo; Januardi; Riswan Aradea (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aimed to improve the learning motivation of vocational high school (SMK) students through the implementation of a digital-based interactive learning model. The research was motivated by the low level of student participation, passive classroom behavior, and the tendency of students to use smartphones for non-academic purposes during lessons. This Classroom Action Research (CAR) was conducted in two cycles involving 30 tenth-grade vocational high school students. Data were collected through observation, questionnaires, and documentation and analyzed using quantitative and descriptive qualitative techniques. The results indicated a significant improvement in students’ learning motivation. The percentage of students categorized as having high learning motivation increased from 60% in Cycle I to 83.3% in Cycle II, exceeding the success indicator of 75%. Students also demonstrated greater participation, confidence, enthusiasm, and engagement during learning activities. The findings suggest that digital-based interactive learning effectively transforms smartphone use into productive learning tools and creates a more active, student-centered, and enjoyable learning environment. This study contributes practical evidence regarding the effectiveness of digital interactive learning in enhancing motivation among vocational high school students.